1968
DOI: 10.1021/je60038a016
|View full text |Cite
|
Sign up to set email alerts
|

Correlated thermal conductivity data of rare gases and their binary mixts. at ordinary pressures

Abstract: Published equilibrium data for 99 aqueous-organic systems, 47 organic-organic systems, and 39 liquid-gas systems have been tested for linearity. The best straight lines which pass either through the origin or through the mean values of the observations are considered. Slopes are tabulated for 28 systems having an error of less than 1% over the concentration range studied experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

1971
1971
1996
1996

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…In contrast, using the force constants suggested by DiPippo and Kestin The mixture thermal conductivity decreases by a factor of 23 as the molecular weight increases from pure helium to pure xenon over the range of mixture temperature in this investigation, and mixture conductivity also Gandhi and Saxena [1968] have observed that the measurements of Mason and von Ubish appear to be systematically higher than others they reviewed.…”
Section: Vyrt= V(5/3)rtcontrasting
confidence: 75%
“…In contrast, using the force constants suggested by DiPippo and Kestin The mixture thermal conductivity decreases by a factor of 23 as the molecular weight increases from pure helium to pure xenon over the range of mixture temperature in this investigation, and mixture conductivity also Gandhi and Saxena [1968] have observed that the measurements of Mason and von Ubish appear to be systematically higher than others they reviewed.…”
Section: Vyrt= V(5/3)rtcontrasting
confidence: 75%
“…in degrees Kelvin and K has units of W/m -K. The conductivi t y of a gas mixture is based on the work of Brokaw< 58 ) and can be determi ned from: conducti vity as given by Equation 56( 57) The accommodation coefficient (a) used in the model calculation is based on results by Ullman et al . (sg) who measured the accornodation coefficients of 5…”
mentioning
confidence: 99%
“…When a similar procedure was adopted at about 90°C for Ne, N2, and 02, the differences in the two sets were less than 0.2%. The correlated values of k as a function of temperature for neon as given by Gandhi and Saxena (6) were used in the data reduction. These studies again establish our contention of the almost complete absence of convection and the procedure of determining conductivity from readings when the platinum wire was heated about 4°C above the bath temperature.…”
mentioning
confidence: 99%